Does Community-Level Social Capital Predict Decline in Instrumental Activities of Daily Living? A JAGES Prospective Cohort Study - Fujihara, Satoko (Int J Environ Res Public Health, 2019)
Instrumental activities of daily living (IADL) represent the most relevant action capacity in older people with regard to independent living. Previous studies have reported that there are geographical disparities in IADL decline. This study examined the associations between each element of community-level social capital (SC) and IADL disability. This prospective cohort study conducted between 2010 and 2013 by the Japan Gerontological Evaluation Study (JAGES) surveyed 30,587 people aged 65 years or older without long-term care requirements in 380 communities throughout Japan. Multilevel logistic-regression analyses were used to determine whether association exists between community-level SC (i.e., civic participation, social cohesion, and reciprocity) and IADL disability, with adjustment for individual-level SC and covariates such as demographic variables, socioeconomic status, health status, and behavior. At three-year follow-up, 2886 respondents (9.4%) had suffered IADL disability. Residents in a community with higher civic participation showed significantly lower IADL disability (odds ratio: 0.90 per 1 standard deviation increase in civic participation score, 95% confidence interval: 0.84–0.96) after adjustment for covariates. Two other community-level SC elements showed no significant associations with IADL disability. Our findings suggest that community-based interventions to promote community-level civic participation could help prevent or reduce IADL disability in older people.